Ngaji Warung Kopi sebagai Upaya Penguatan Pendidikan Karakter Kepedulian Sosial Pemuda di Kecamatan Kenjeran Kota Surabaya - Khoirur Rojikhin; Muhammad Turhan Yani (Kajian Moral dan Kewarganegaraan, 2023)
Education can be obtained anywhere and anytime and with anyone. Both in the school environment (formal), the family environment (informal) and in the community (non-formal). One form of non-formal education is Gemmar (Maghrib Community Movement) Koran as an effort by the government to shape personality and prevent moral decay. However, these activities did not run optimally in the Kenjeran sub-district of the city of Surabaya. Through Ngaji Warung Kopi, the youths modify the meaning of “Ngaji” into a form of non-formal education that is more comfortable and enjoyable as an activity that is sought to strengthen the character education of youth social care. This study aims to find out how the Koran coffee shop activity can be an effort to strengthen character education for social awareness of youth in Kenjeran sub-district, Surabaya. The theory used in this study is the symbolic interactionism of Robert Herbert Mead and Herbert Blumer, who explain that Social Interaction creates a meaning and develops a self-concept that gives an individual's motive for behavior. This research was conducted at the Bintang Sembilan Coffee Shop, Kenjeran district, Surabaya. There were four informants in this study who were selected by purposive sampling. The focus of this research is the initiation to the implementation of the Koran coffee shop activity. Data were collected through interactive observation and in-depth interviews. The results of strengthening youth character education are shown through the behavior of various likes to orphans and orphans such as food, drinks to monthly pocket money whose behavioral motives are generated by self-concept which is developed through interactions that occur in coffee shop Koran activities which are the result of modifications to the meaning of "recite the Koran". ” which is more adapted to the habits of youth in the Kenjeran sub-district, Surabaya. Keywords: Strengthening Character Education, Social Awareness, Ngaji, Coffee Shop.